2013
DOI: 10.1016/j.jhealeco.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Does retirement age impact mortality?

Abstract: The relationship between retirement and mortality is studied with a unique administrative data set covering the full population of Norway. A series of retirement policy changes in Norway reduced the retirement age for a group of workers but not for others. Difference-in-differences estimation based on monthly birth cohorts and treatment group status show that the early retirement programme significantly reduced the retirement age; this holds true also when we account for programme substitution, for example int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 29 publications
1
80
1
1
Order By: Relevance
“…Among the studies reviewed in Table 12 that investigate gender heterogeneity, a majority find no significant differences in health outcomes between men and women. Moreover, studies that use a reform-based approach suggest that the potential gender differences are likely to be small or even zero (see, e.g., Hernaes et al 2013;Atalay and Barrett 2014;de Grip et al 2012). A similar picture is acquired from the related literature on the health effects of job loss.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Among the studies reviewed in Table 12 that investigate gender heterogeneity, a majority find no significant differences in health outcomes between men and women. Moreover, studies that use a reform-based approach suggest that the potential gender differences are likely to be small or even zero (see, e.g., Hernaes et al 2013;Atalay and Barrett 2014;de Grip et al 2012). A similar picture is acquired from the related literature on the health effects of job loss.…”
Section: Resultsmentioning
confidence: 83%
“…The 2SLS estimation allows me to compare the precision of the mortality estimates to those of two previous studies. The most comparable study is Hernaes et al (2013) who investigate the mortality effects of lowering the early retirement age for a group of Norwegian workers using a similar difference-in-difference strategy as in this paper. They find that a 1-year increase in the actual retirement age results in a 0.2% point increase in mortality by age 70 (insignificant), which is somewhat smaller than what I find for mortality by age 69 (0.34% points).…”
Section: The Effects Of Retirement On Healthmentioning
confidence: 99%
“…We therefore use characteristics of the pension schemes to construct instrumental variables for retirement, and use 2SLS to estimate the retirement effect. Hernaes et al (2013) suggested this kind of instrumenting in an analysis of retirement and mortality.…”
Section: Instrument Variable Analysis Of Retirementmentioning
confidence: 99%
“…Snyder and Evans (2006) conclude that employment past retirement age decreases mortality. However, Hernaes et al (2013) find no significant effect of retirement on mortality, while Blake and Garrouste (2013), Bloemen et al (2013) and Hallberg et al (2014) even find that retirement leads to a decrease in mortality.…”
Section: Introductionmentioning
confidence: 98%